What's the Long-Term Impact of Conditional Cash Transfers on Education? - World Bank (Washington, DC, 2014)
Cash transfers are used around the world to better encourage poor families to take advantage of educational offerings by offering financial incentives that can boost their income. The Colombia study shows that these can be an important tool not only for encouraging families to enroll their children in school, but also keeping them there. Indeed, the results indicate that students whose families received the cash transfers were more likely to graduate high school, an educational milestone that opens doors to higher education and in developing countries especially, increases employment opportunities. The study showed that higher enrollment, and improved graduation rates, didn't necessarily translate into better learning. Students whose families received the cash transfers didn't show improvements in test scores when compared with students whose families didn't receive the money. It may be that teachers need better training to address the needs of low-income students, or more resources may be required for struggling students. Future research could consider linking cash transfers to school performance, to see whether this incentive encourages students (and their parents) to pay more attention to learning. As part of this, researchers would have to consider what support low-income households might need to monitor and assist their children in school. The Colombia study makes an important contribution to the body of evidence on the effectiveness of cash transfers in keeping kids in school and raising graduation rates. The next step is to understand how cash transfers, or other programs, can successfully be used to boost learning too.